Effect of Boiled Egg White Consumption on Healing of Sewing Wounds in Postpartum Mothers Post Sectio Caesarea - Naili Rahmawati; Ani Casniah; Haidir Syafrullah; Dian Purnamasari (Jurnal Penelitian Pendidikan IPA, 2025)
Sectio Caesarea is a type of delivery that is continuously increasing in the current era, both for medical reasons and baby factors, however, the surgical procedure for SC delivery can cause several complications, one of which is Surgical Wound Infection (ILO), when the body experiences injuries. large, the body needs a lot of protein, the protein most easily found by people is eggs, one egg contains 6-8 grams of protein, because of this, boiled eggs are recommended for consumption during post-cesarean section operations. The aim of this study was to determine the effect of giving boiled egg whites on post-caesarean wound healing. Methodology of this research uses quantitative with a true experiment two groups pre and post test with control, the sample in this study is 20 interventions and 20 controls, univariate analysis in this study uses a frequency distribution while bivariate analysis uses Wilcoxon. Result pre-test of the intervention and control groups, it was found that all respondents had wounds less than 100%, however, during the post-test, most respondents had poor wound healing results of 55% in the control group, and the majority of respondents had good wound healing results of 90%. in the intervention group after being given boiled egg whites. After carrying out the analysis, a p-value of 0.000 was obtained for the intervention and control groups. Concluded that boiled eggs have an influence on healing caesarean section wounds. This research can provide information regarding the effect of egg whites on the healing process of post-cesarean section wounds.